Insight into the Salivary Gland Transcriptome of Lygus lineolaris (Palisot de Beauvois) - Showmaker, Kurt C; Bednářová, Andrea; Gresham, Cathy; Hsu, Chuan-Yu; Peterson, Daniel G; Krishnan, Natraj (PLoS One, 2016)
The tarnished plant bug (TPB), Lygus lineolaris (Palisot de Beauvois) is a polyphagous, phytophagous insect that has emerged as a major pest of cotton, alfalfa, fruits, and vegetable crops in the eastern United States and Canada. Using its piercing-sucking mouthparts, TPB employs a "lacerate and flush" feeding strategy in which saliva injected into plant tissue degrades cell wall components and lyses cells whose contents are subsequently imbibed by the TPB. It is known that a major component of TPB saliva is the polygalacturonase enzymes that degrade the pectin in the cell walls. However, not much is known about the other components of the saliva of this important pest. In this study, we explored the salivary gland transcriptome of TPB using Illumina sequencing. After in silico conversion of RNA sequences into corresponding polypeptides, 25,767 putative proteins were discovered. Of these, 19,540 (78.83%) showed significant similarity to known proteins in the either the NCBI nr or Uniprot databases. Gene ontology (GO) terms were assigned to 7,512 proteins, and 791 proteins in the sialotranscriptome of TPB were found to collectively map to 107 Kyoto Encyclopedia of Genes and Genomes (KEGG) database pathways. A total of 3,653 Pfam domains were identified in 10,421 sialotranscriptome predicted proteins resulting in 12,814 Pfam annotations; some proteins had more than one Pfam domain. Functional annotation revealed a number of salivary gland proteins that potentially facilitate degradation of host plant tissues and mitigation of the host plant defense response. These transcripts/proteins and their potential roles in TPB establishment are described.
Keywords: Heteroptera; Salivary Glands; hmyzí geny; slinné žlázy; Animals; stanovení celkové genové exprese; Genes, Insect; genová ontologie; zvířata; anotace sekvence; Gene Expression Profiling; Gene Ontology; Molecular Sequence Annotation